2015
DOI: 10.1021/acs.jpca.5b08892
|View full text |Cite
|
Sign up to set email alerts
|

Role of Organic Coatings in Regulating N2O5 Reactive Uptake to Sea Spray Aerosol

Abstract: Previous laboratory measurements and field observations have suggested that the reactive uptake of N 2 O 5 to sea spray aerosol particles is a complex function of particle chemical composition and phase, where surface active organics can suppress the reactive uptake by up to a factor of 60. To date, there are no direct studies of the reactive uptake of N 2 O 5 to nascent sea spray aerosol that permit assessment of the role that organic molecules present in sea spray aerosol (SSA) may play in suppressing or enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 58 publications
1
62
0
Order By: Relevance
“…29,30 Interestingly, studies seeking to replicate microbial blooms in a controlled manner (using informed representative organic species for each stage of the bloom) showed that N 2 O 5 uptake on SSA did not differ significantly from simplistic laboratory-generated NaCl particles (see Figure 3b). 31 This implies either (1) the complex nature of the organic species result in loose surface packing 20,32 or (2) the organic species are well mixed or present in low enough concentrations so as not to impact uptake. Both have significant implications for understanding how chemical changes dictate aerosol climate properties (i.e., heterogeneous reactivity, hygroscopicity, and interaction with solar radiation).…”
Section: ■ Chemistry-driven Interactions Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Interestingly, studies seeking to replicate microbial blooms in a controlled manner (using informed representative organic species for each stage of the bloom) showed that N 2 O 5 uptake on SSA did not differ significantly from simplistic laboratory-generated NaCl particles (see Figure 3b). 31 This implies either (1) the complex nature of the organic species result in loose surface packing 20,32 or (2) the organic species are well mixed or present in low enough concentrations so as not to impact uptake. Both have significant implications for understanding how chemical changes dictate aerosol climate properties (i.e., heterogeneous reactivity, hygroscopicity, and interaction with solar radiation).…”
Section: ■ Chemistry-driven Interactions Betweenmentioning
confidence: 99%
“…28 Segment B shows results that N 2 O 5 uptake is not suppressed in the presence of complex organics produced over the course of a microbial bloom. 31 Segment C illustrates a previously unrecognized reaction pathway for HNO 3 with functional groups present in bioorganic molecules produced during microbial blooms. 34 Segment D shows a previously unrealized competition between aromatic organics and Cl − for NO 2 + resulting from N 2 O 5 uptake to a surface.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…organic component of the particle. 88 The calculated OVF as a function of particle size for the 1 : 1 mass ratios of NaCl/glucose and NaCl/laminarin is shown in Fig. 4C.…”
Section: Interactions Of Water Vapor With Mixtures Of Sodium Chlormentioning
confidence: 99%
“…[304][305][306] In the atmosphere, they can alter the exchange between the gas phase and clouds, fogs and particles, [307][308][309][310][311][312][313] change the kinetics of reactions such as the hydrolysis of NO 2 (ref. 173) and the oxidation of organics, 268,314,315 and alter ion composition and chemistry at the interface.…”
Section: Organicsmentioning
confidence: 99%
“…555,560 Organic coatings also appear to decrease N 2 O 5 uptake on particles, although this may be sensitive to the relative amounts of water present (and hence relative humidity) as well as the viscosity of the organic coating. 312,313,556,[561][562][563][564][565][566][567] If chloride ions are present, there is a competing reaction to form nitryl chloride, ClNO 2 . [568][569][570][571][572][573] It is interesting that the chloride ion reaction occurs at the interface, while that with water occurs deeper into the bulk of the particle.…”
Section: Biogenic-anthropogenic Synergies In the Anthropocenementioning
confidence: 99%